2016
DOI: 10.1016/j.rvsc.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Feed exposure to FB1 can aggravate pneumonic damages in pigs provoked by P. multocid a

Abstract: The possible interaction between Pasteurella multocida and the mycotoxin fumonisin B1 (FB1), recognised as one of the most often food/feed contaminant, was studied with the aim to evaluate whether and how FB1 can influence and/or complicate the development and severity of various pathological damages provoked by Pasteurella multocida in some internal organs of pigs. Heavier lung pathology was seen in pigs experimentally infected with Pasteurella multocida, when the same were exposed to 20 ppm dietary levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…In the present investigation, the most striking modifications seen in the liver of piglets exposed to 20 mg FB 1 /kg diet are the vacuolar degeneration of hepatocyte cytoplasm. This finding was markedly categorized as a mild to moderate effect, in agreement with the findings of Dilkin et al [20] and Kovács et al [21]. The vacuolar degeneration of hepatic cell cytoplasm is highly associated with disturbance of cellular water or lipid metabolism, indicative of an exertion of the cell’s metabolic and/or detoxification activity.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In the present investigation, the most striking modifications seen in the liver of piglets exposed to 20 mg FB 1 /kg diet are the vacuolar degeneration of hepatocyte cytoplasm. This finding was markedly categorized as a mild to moderate effect, in agreement with the findings of Dilkin et al [20] and Kovács et al [21]. The vacuolar degeneration of hepatic cell cytoplasm is highly associated with disturbance of cellular water or lipid metabolism, indicative of an exertion of the cell’s metabolic and/or detoxification activity.…”
Section: Discussionsupporting
confidence: 89%
“…Despite a recent study illustrating that 12.2 mg FBs/kg diet developed hepatotoxicity in piglets after 28 days of exposure [10], it is interesting to study the sub-acute effect of FB 1 on the liver. From this point of view, earlier reports which applied 20 mg FB 1 /kg diet [18,21] on piglets did not provide alteration in the membrane profile of the liver, in connection with its hepatotoxicity. Monitoring alterations in lipids may assist for better understanding of FB 1 toxicity mechanism of action.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…FB1 also significantly increases colonization of the small and large intestine by extra-intestinal pathogenic E. coli strains [ 95 ]. Some studies have shown that administration of different doses of FB1 (11.8 mg/kg, 0.5 mg/kg, and 20 mg/kg) can complicate the infection process of Bacillus subtilis A, causing interstitial bronchial pneumonia [ 96 , 97 , 98 ]. Recent studies have shown that non cytotoxic doses of FB1 can aggravate OTA induced cytotoxicity and apoptosis.…”
Section: Toxic Effects Of Fb1mentioning
confidence: 99%